2008
DOI: 10.1007/s00134-008-1271-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional cooling of the extracorporeal blood circuit: a novel anticoagulation approach for renal replacement therapy?

Abstract: Objective: To test the hypothesis that cooling of blood in the extracorporeal circuit of continuous veno-venous hemofiltration (CVVH) enables to realize the procedure without the need of anticoagulation. Design: Experimental animal study. Methods: We developed the device for selective cooling of extracorporeal circuit (20°C) allowing blood rewarming (38°C) just before returning into the body. Twelve anesthetized and ventilated pigs were randomized to receive either 6 h of CVVH with application of this device (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Furthermore, the beneficial effect of cooling on the life span of the extracorporeal circuit has been suggested [19]. In our series, the relatively short duration of the temperature variation period and the limited number of patients did not allow evaluation of the impact of modest hypothermic temperature on the potential reduction in extracorporeal clotting and we did not evaluate the consequences of the two regimen of temperature on blood coagulation tests.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the beneficial effect of cooling on the life span of the extracorporeal circuit has been suggested [19]. In our series, the relatively short duration of the temperature variation period and the limited number of patients did not allow evaluation of the impact of modest hypothermic temperature on the potential reduction in extracorporeal clotting and we did not evaluate the consequences of the two regimen of temperature on blood coagulation tests.…”
Section: Discussionmentioning
confidence: 92%
“…In conclusion, the data from this particular study, as well as from our previous experimental studies, show that hypothermal coagulopathy could also be a good servant and not only a bad master [8,9]. It was proven that cooling brought the blood into a complete noncoagulation status -a condition that can otherwise only be reached using chemical anticoagulants.…”
Section: Discussionmentioning
confidence: 72%
“…In our experimental study, this selective ECC cooling device was shown effective in preserving the circuit from clotting for several hours without the need of any anticoagulants. Although the efficiency of this cooling device was very good, the patency of the circuit was not retained for the planned 24-h period in all experiments [8,9]. One of the plausible explanations is that the decrease in blood temperature to 208C was not sufficient for some of animals -we can speculate that the response of an individual coagulation system to a certain temperature may not be always uniform.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Based on these observations, Krouzecky and colleagues now report on the deliberate cooling of blood in the extracorporeal CRRT circuit down to a temperature of 20°C as a novel technique for regional anticoagulation in an experimental porcine model [16]. This study randomized 12 anesthetized and ventilated pigs to 6 h of CRRT (neutral fluid balance, 20 mL/kg per h) with either regional blood cooling of the extracorporeal circuit (hypothermic circuit) or control (isothermic circuit).…”
mentioning
confidence: 99%